UPAYA PENINGKATAN COLLABORATION SKILLS MELALUI PEMBELAJARAN PROBLEM BASED LEARNING (PBL) di KELAS V SDN TINGKIR TENGAH 02 SALATIGA - Muhammad Iqbal Maruf; Mawardi (STKIP Subang, 2023)
ABSTRACT The research was conducted with the aim of improving collaboration skills in 5th grade elementary school students using the Problem Based Learning (PBL) instructional model. The study took place at SDN Tingkir Tengah 02 Salatiga in the first semester of the 2023/2024 academic year, with a total of 28 students. This research is a Classroom Action Research with non-test data collection techniques, and quantitative data analysis. The instrument used was an observation sheet for collaboration skills. The research consisted of two cycles. The results of the research showed that the Problem Based Learning instructional model can enhance collaboration skills. This was evidenced by the pre-cycle data, where only 32.14% of the fifth-grade students exhibited good collaboration skills, while 67.86% were still lacking in collaboration skills. In the first cycle, there was an increase to 53.57% of students with good collaboration skills, while 46.43% of students still had insufficient collaboration skills. In the second cycle, there was a further improvement, with 82.57% of students demonstrating good collaboration skills, and 17.43% of students still lacking in collaboration skills. This improvement was evident in changes in student behavior, as students in the pre-cycle appeared to prefer working individually, but after the implementation of this model, students were very enthusiastic about collaboration. Keywords: Collaboration Skills, Problem Based Learning (PBL) ABSTRAK Penelitian dilaksanakan dengan tujuan untuk meningkatkan collaboration skils pada siswa kelas 5 Sekolah Dasar dengan menggunakan model pembelajaran Problem Based Learning (PBL). Penelitian dilaksanakan di SDN Tingkir Tengah 02 Salatiga pada kelas 5 Semester 1 tahun pelajaran 2023/2024 dengan jumlah siswa 28 orang. Jenis penelitian ini adalah Penelitian Tindakan Kelas dengan teknik pengumpulan data nontes, analisis data berupa kuantitatif. Intrumen yang digunakan adalah lembar observasi collaboration skills. Penelitian dilaksanakan dua siklus. Hasil penelitian menunjukkan bahwa model pembelajaran Problem Based Learning dapat meningkatkan collaboration skills. Dibuktikan dengan data pra siklus dari 28 siswa kelas 5 hanya 32,14% siswa yang collaboration skills baik, sedangkan 67,86% masih kurang dalam collaboration skills. Pada siklus I mengalami kenaikan menjadi 53,57% siswa dengan collaboration skills baik, sedangkan untuk siswa yang kurang dalam collaboration skills menjadi 46,43%, pada siklus II mengalami peningkatan menjadi 82,57% siswa dengan kemampuan collaboration skills yang baik dan 17,43% siswa yang masing kurang dalam collaboration skills. Peningkatan tersebut nampak pada perubahan perilaku siswa dimana siswa pada pra siklus terlihat lebih memilih bekerja secara individu sedangkan setelah penerapan model ini siswa sangat antusias untuk berkolaborasi. Kata Kunci: Collaboration Skills, Problem Based Learning (PBL)